Lexicon Latinopolonicum Jana Warty – unikatowy „druk widmo” z tajemnicą w tle (PDF 8,57 MB) (Książnica Śląska, 2025)
The subject of the text is the old print “Lexicon Latinopolonicumto iest Dictionarz per ordinem literarum dostatecznie po Łaciniezebrany…” by Jan Warta, published in Kraków in 1616. This print remains unique in Poland, and until 1961 it was known only from bibliographic notes. The article collects the available fragmentary information about the dictionary kept in the Silesian Library in Katowice(ref. 220347 I). The author analyzes the history and characteristicfeatures of the dictionary and his lexicographic aspect. In this textthe work of Jan Mączyński “Lexicon Latino Polonicum ex optimis Latinae linguae Scriptoribus concinnatum…” (published in Königsbergin 1564) is identified as the main source for the dictionary